Sistem Manajemen Toko Perhiasan Perak menggunakan Progressive Web App (Studi Kasus: Toko Borneo Silver Banjarmasin) - Benyamin Fajri; Achmad Arwan; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Borneo Silver store is one of the silver jewelry stores in Banjarmasin. This store sells various types of silver jewelry such as necklaces, rings, bracelets, foot pendants, earrings, and jewelry accessories. This store performs online sales transactions, offline sales, purchases, and custom sales. This shop has a branch that specializes in offline sales of second-hand silver jewelry. Borneo Silver store still uses written invoices as proof of transactions and calculations manually using a calculator. In addition, this store also does not have a record of every item so it cannot know directly whether the stock is still available. The process of calculating financial reports at this store is also taking a long time because they have to calculate manually from sales notes and purchase notes. To solve these problems, a Silver Jewelry store management system was created using a Progressive Web App with the main features of online sales, offline sales, purchases, custom sales, and financial reports. Then proceed with the design and implementation stages. This system is built using the PHP programming language, the Lumen framework, and the Lighthouse framework as the backend and the Ionic framework as the frontend. After the implementation phase, it is continued with the testing phase. Tests are carried out using unit testing, integration testing, and validation testing methods. The tests carried out resulted in 100% valid so that the system made was in accordance with the results of requirements analysis and design.